Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.ppat.1009416
|View full text |Cite
|
Sign up to set email alerts
|

Viral genomic, metagenomic and human transcriptomic characterization and prediction of the clinical forms of COVID-19

Abstract: COVID-19 is characterized by respiratory symptoms of various severities, ranging from mild upper respiratory signs to acute respiratory failure/acute respiratory distress syndrome associated with a high mortality rate. However, the pathophysiology of the disease is largely unknown. Shotgun metagenomics from nasopharyngeal swabs were used to characterize the genomic, metagenomic and transcriptomic features of patients from the first pandemic wave with various forms of COVID-19, including outpatients, patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Studies during previous SARS and Middle East respiratory syndrome (MERS) epidemics showed that individuals receiving invasive mechanical ventilation were more likely to develop secondary infections and have a higher fatality rate ( Feldman and Anderson, 2021 ). Recent investigations indicate that coinfections and/or superinfections occur at varying frequencies in oral, blood and urine samples from COVID-19 patients ( Charalampous et al, 2020 ; Langford et al, 2020 ; Mostafa et al, 2020 ; Alhumaid et al, 2021 ; Ripa et al, 2021 ; Rodriguez et al, 2021 ; Silva et al, 2021 ; Vijay et al, 2021 ). However, little is known about the prevalence of these pathogens and their exact molecular relevance in the human lung tissue during COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies during previous SARS and Middle East respiratory syndrome (MERS) epidemics showed that individuals receiving invasive mechanical ventilation were more likely to develop secondary infections and have a higher fatality rate ( Feldman and Anderson, 2021 ). Recent investigations indicate that coinfections and/or superinfections occur at varying frequencies in oral, blood and urine samples from COVID-19 patients ( Charalampous et al, 2020 ; Langford et al, 2020 ; Mostafa et al, 2020 ; Alhumaid et al, 2021 ; Ripa et al, 2021 ; Rodriguez et al, 2021 ; Silva et al, 2021 ; Vijay et al, 2021 ). However, little is known about the prevalence of these pathogens and their exact molecular relevance in the human lung tissue during COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies during previous SARS and MERS epidemics showed individuals receiving invasive mechanical ventilation were more likely to develop secondary infections and have a higher fatality rate (Feldman & Anderson, 2021). Recent investigations indicate that coinfections and/or superinfections occur at varying frequencies in oral, blood, and urine samples from COVID-19 patients (Alhumaid et al, 2021; Charalampous et al, 2020; Langford et al, 2020; Mostafa et al, 2020; Ripa et al, 2021; Rodriguez et al, 2021; Silva et al, 2021; Vijay et al, 2021). However, little is known about the prevalence of these pathogens and their exact molecular relevance in the human lung tissue during COVID-19 infection.…”
Section: Introductionmentioning
confidence: 99%
“…to evolve and interact together along with SARS-CoV-2. 18 Worryingly, the coexistence of other microbial pathogens and underlying intricate molecular pathogenesis leading to exorbitant indisposition in severely ill COVID-19 patients. 19 In this scenario, empiric broad-spectrum use of antibiotics has been prescribed for the majority of the COVID-19 patients irrespective of the cause.…”
Section: Introductionmentioning
confidence: 99%
“…This technology allows to detect and describe a wide range of known and unknown emerging pathogens, including their virulence and/or AMR profiles. 18 This study thus was carried out to precisely analyze the meta-transcriptomic sequencing data to reveal the genomic and metagenomic features among vaccinated and nonvaccinated populations, though the complete host−pathogen interaction may not be elucidated.…”
Section: Introductionmentioning
confidence: 99%